Analisis Kepuasan Pelayanan Kesehatan Terhadap Pasien di Puskesmas Sekar Jaya Kabupaten Ogan Komering Ulu - Rismaniar,; Chairil Zaman; Dian Anggreny (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2022)
The existence of health service facilities affects the health status of the people of a country (Kemenkes RI, 2020). The level of patient satisfaction is considered as a very important dimension, quality and is one of the main indicators. The purpose of this study was to look at the factors associated with patient satisfaction. This study uses a quantitative method with a Cross Sectional approach. Statistical test using Chi Square test. Multivariate analysis in this study used multiple logistic regression analysis. In this study, it can be concluded that there is no relationship between age (p = 0.815) Tangibles (p = 0.567) with satisfaction at the Sekar Jaya Health Center, OKU Regency in 2021. There is a relationship between sex (p = 0.005; OR = 2.415), Reliability (p = 0.027 ; OR = 2,303), Responsiveness (p = 0.000; OR = 4.770), Assurance (p = 0.045; OR = 1.888) and Empathy (p = 0.000; OR = 8.737) with satisfaction at the Sekar Jaya Health Center, OKU Regency in 2021). The most dominant variable was gender (p=0.035; OR=2.261). Suggestions for especially the Sekar Jaya Health Center in OKU Regency to pay attention to Tangibles, Reliability, Responsiveness and Empathy. To improve service and better performance, researchers suggest emphasizing empathy for patients. Gender is the most important factor to consider.